2021
DOI: 10.1088/1755-1315/713/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Artocarpus heterophyllus leaves extract improve facial skin in clay mask formulation

Abstract: Artocarpus heterophyllus (A.heterophyllus) is one of plants that commonly used for skin care. This study aimed to formulate a clay mask preparation with the active ingredient A.heterophyllus 3% leaf extract and evaluating its activities in repairing facial moisture, smoothness, large pores, blemishes and wrinkles. The process of providing clay masks begins with the preparation of Artocarpus heterophyllus leaf etanol extracts with standardized quality, preparation of clay mask bases with guaranteed quality, mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…These results suggested that the studied clay mask is effective in mitigating prominent skin issues such as acne, hyperseborrhea, and skin dehydration, indicating immediate skin barrier enhancement. Various clinical trials have demonstrated the efficacy of commonly used clay minerals, including kaolin and bentonite for oily skin management, supporting the current results 10–12 . Kaolin and bentonite are hydrated Aluminum Silicate and Aluminum Magnesium Silicate, respectively.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These results suggested that the studied clay mask is effective in mitigating prominent skin issues such as acne, hyperseborrhea, and skin dehydration, indicating immediate skin barrier enhancement. Various clinical trials have demonstrated the efficacy of commonly used clay minerals, including kaolin and bentonite for oily skin management, supporting the current results 10–12 . Kaolin and bentonite are hydrated Aluminum Silicate and Aluminum Magnesium Silicate, respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Various clinical trials have demonstrated the efficacy of commonly used clay minerals, including kaolin and bentonite for oily skin management, supporting the current results. [10][11][12] Kaolin and bentonite are hydrated Aluminum Silicate and Aluminum Magnesium Silicate, respectively. They have the ability to absorb oil due to their large surface area, porosity, ionic charge, which make them effective ingredients in products designed to control oiliness.…”
Section: Discussionmentioning
confidence: 99%
“…These chemical constituents are responsible for their pharmacological activities. The previous study demonstrated its leaves effect that benefits facial skincare by improving moisture, smoothness, pore size, blemishes, and wrinkles ( 4 - 6 )…”
Section: Introductionmentioning
confidence: 99%